Muddy Boots and Smart Suits Researching Asia-Pacific Affairs. - Farrelly, Nicholas; King, Amy; Wesley, Michael; White, Hugh ([S.l.] : ISEAS - Yusof Ishak Institute, 2017)
From grassroots conflicts to great power relations, this book explores some of the key concepts, methodologies, and dilemmas of researching Asia-Pacific affairs. The book deals with key questions about the Asia Pacific: Why should we study policy from the'ground up'? What are the human considerations for societies in conflict? Why is regionalism important and how do global powers play a role? Should Asia-Pacific researchers embrace the design-based revolution in the social sciences? Muddy Boots and Smart Suits is for students, scholars, and policymakers in the region looking for a new way to understand local, regional, and global security challenges
Muddy Boots and Smart Suits: Researching Asia-Pacific Affairs -- Contents -- About the Contributors -- 1. Introduction to Research in Asia-Pacific Affairs -- Section I. In the Field -- 2. Studying Policy from the Ground Up: The Solomon Islands Case -- 3. Reflections on Political Cultures in Thought and Action -- 4. Human Considerations in Conflicted Societies -- Section II. Analysing Politics -- 5. The Design-based Revolution in Comparative Politics -- 6. Count Me In: Quantitative Research in Asia-Pacific Affairs -- Section II. Shaping a Region -- 7. History, Conflict, and Contexts: Remembering World War II in Asia -- 8. Regionalism and Global Powers -- Section IV. Conflict and Order -- 9. War and Order: Thinking about Military Force in International Affairs -- 10. Power, Prestige, and Order -- 11. Strategic Culture in the Asia-Pacific: Putting Policy in Context -- Section IV. Policy and Practice -- 12. Securing the Local and the Global: The Story of Policy Engagement -- 13. Muddy Boots and Smart Suits: Practical Considerations for Research in the Twenty-first Century -- Bibliography -- Index.
Includes bibliographical references and index.
Keywords: International relations